Volatilome: A Novel Tool for Risk Scoring in Ischemic Heart Disease - Marzoog, Basheer Abdullah (Current Cardiology Reviews, 2024)
Developing a novel risk score for accurate assessment of cardiovascular disease (CVD) morbidity and mortality is an urgent need in terms of early prevention and diagnosis and, thereafter, management, particularly of ischemic heart disease. The currently used scores for the evaluation of cardiovascular disease based on the classical risk factors suffer from severe limitations, including inaccurate predictive values. Therefore, we suggest adding a novel non-classical risk factor, including the level of specific exhaled volatile organic compounds that are associated with ischemic heart disease, to the SCORE2 and SCORE2-OP algorithms. Adding these non-classical risk factors can be used together with the classical risk factors (gender, smoking, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, diabetes mellitus, arterial hypertension, ethnicity, etc.) to develop a new algorithm and further program to be used widely.
Keywords: SCORE2-OP